Psychological hardiness and social support as protective factors against burnout in high-performance athletes - Oleas, D.; Rubio, D. A.; del Pilar Méndez-Sánchez, M.; Trujillo, M.; Jaenes, J. C. (Frontiers in Sports and Active Living, 2025)
Burnout Syndrome (BOS) is a psychological condition characterized by emotional exhaustion, depersonalization, and a reduced sense of accomplishment, frequently observed in high-performance athletes exposed to chronic stress and competitive pressure. This study examined the role of hardiness and social support as potential protective factors against burnout and its dimensions while accounting for demographic and sports-related variables such as age, sex, and level of competition. The sample comprised 388 high-performance athletes aged between 15 and 45 years (46% women; M = 27.31, SD = 8.51). Participants completed the validated Spanish versions of the Athlete Burnout Questionnaire (ABQ), Resilient Personality Scale for Marathoners (EPRM), and Social Support Scale (EAS). The data were analyzed using nonparametric tests (Kruskal-Wallis test) and multiple linear regression models. The results revealed that sex was not a significant predictor of burnout, whereas age and competition level were negatively associated with overall burnout scores. Among the psychological variables, hardiness, particularly commitment and control dimensions, emerged as the strongest protective factor, whereas social support was negatively associated with emotional exhaustion and total burnout. The significant interaction between social support and competition level indicated that younger athletes had a stronger protective effect than senior athletes. These results show that social support plays a different role in competitive stages, indicating early reinforcement of athletes' social networks can significantly lower their burnout risk. Practical implications for coaches and sports psychologists in developing integrated prevention and intervention programs that enhance athletes' hardiness and social connection throughout their careers.